Dystocia in Goat Due to Dropsy of Fetus Born Co-Twin with Live Fetus - Koli, Anujkumar Bramhadev; Patil, Anil Dinkarrao; Ramteke, Snehal Shalik; Naktar, Sonali Baburao (The Indian Journal of Animal Reproduction, 2023)
A non- descript goat of 6 years’ age was presented to TVCC, COVAS, Udgir with the history of dystocia. The case was already handled by local non – technical person. The goat was examined for fetal position and presentation. A live male fetus was removed with gentle traction and another fetus with ascites was removed with obstetrical manipulation and partial fetotomy. A successful management of dystocia in non – descript goat due to dropsy of the fetus born co-twin along with normal fetus is achieved after three days treatment.